2016
DOI: 10.4132/jptm.2016.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Expression of MicroRNA-21 in Advanced Colorectal Cancer Patients with Distant Metastases

Abstract: Background:The aim of this study was to determine the regional heterogeneity and clinicopathological significance of microRNA-21 (miR-21) in advanced colorectal cancer (CRC) patients with distant metastasis.Methods:miR-21 expression was investigated by using locked nucleic acid– fluorescence in situ hybridization in the center and periphery of the primary cancer and in distant metastasis from 170 patients with advanced CRC. In addition, α-smooth muscle actin and desmin were evaluated to identify cancer-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…The tissue microarrays (TMAs) were made from the representative 2‐mm cores selected by an experienced gastrointestinal pathologist (H.S.L. ), as described previously (SuperBioChips Laboratories, Seoul, Republic of Korea) .…”
Section: Methodsmentioning
confidence: 99%
“…The tissue microarrays (TMAs) were made from the representative 2‐mm cores selected by an experienced gastrointestinal pathologist (H.S.L. ), as described previously (SuperBioChips Laboratories, Seoul, Republic of Korea) .…”
Section: Methodsmentioning
confidence: 99%
“…In pancreatic ductal adenocarcinoma, miR-21 is commonly associated with tumor metastasis and closely related to poor prognosis [104]. Clinicopathological findings confirmed that the stromal expression of miR-21 in colorectal cancer patients is closely related to distant metastasis [105]. …”
Section: Introductionmentioning
confidence: 99%
“…The collected tissue samples were remaining samples after proper histologic diagnosis and relevant molecular study. Representative tissue areas were reviewed and selected for the construction of tissue microarray (TMA) as described previously [9].…”
Section: Patients and Specimensmentioning
confidence: 99%